Pemanfaatan Tempurung Lontar Dan Zeolit Alam Sebagai Media Vertical Roughing Filter Pada Pengolahan Limbah Cair Tahu - Da Costa, Madalena; Leko, Leonardus Lewa (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2025)
Tofu as a protein food that is favored by the public causes the tofu industry to continue to increase. The tofu industry produces liquid waste that contains high organic matter and has the potential to pollute the environment if not treated. This study aims to determine the ability of activated carbon of palm shell and zeolite as filter media in Vertical Roughing Filter (VRF), in reducing BOD, COD, TSS parameters in tofu liquid waste. The research was carried out in three stages; first, sampling and initial analysis of tofu wastewater characteristics; second, preparing filter media through carbonization and activation; third, making a VRF circuit and treating tofu wastewater, then analyzing the final concentration. The research variables used were flow rate of 0.3 L/m; 0.5 L/m and contact time; 0.5 hours; 1 hour; 2 hours; 4 hours; 8 hours; 16 hours. The results showed that the filter media in VRF was able to reduce BOD, COD, TSS parameters in tofu liquid waste. The highest reduction efficiency was found at a flow rate of 0.3 L/m with a BOD value of 30.25% (contact time 0.5 hours); COD of 67.69 (contact time 1 hour); TSS of 81.56% contact time (0.5 hours). While the flow rate of 0.5 L/m, has a lower efficiency of reducing BOD, COD and TSS than the flow rate of 0.3 L/m. Overall, VRF is able to reduce the content of waste contaminants.